Delamination in plastic packages - Mena, Manolo G. (Philippine Engineering Journal)
Delamination or the disbonding of the plastic moulding compound from various surfaces and interfaces in a packaged integrated circuit is a major cause of reliability failures. This paper reviews the causes of the said disbonding, the types of reliability failures that may be induced as well as various solutions available to prevent delamination.